Therapy Resistance in Cancers: Phenotypic, Metabolic, Epigenetic and Tumour Microenvironmental Perspectives - Zahan, Tasnim; Das, Plabon K.; Akter, Syeda F.; Habib, Rowshanul; Rahman, Md. H.; Karim, Md. Rezaul; Islam, Farhadul (Anti-Cancer Agents in Medicinal Chemistry, 2020)
Background: Chemoresistance is a vital problem in cancer therapy where cancer cells develop mechanisms to encounter the effect of chemotherapeutics, resulting in cancer recurrence. In addition, chemotherapy- resistant leads to the formation of a more aggressive form of cancer cells, which, in turn, contributes to the poor survival of patients with cancer. Objective: In this review, we aimed to provide an overview of how the therapy resistance property evolves in cancer cells, contributing factors and their role in cancer chemoresistance, and exemplified the problems of some available therapies. Methods: The published literature on various electronic databases including, Pubmed, Scopus, Google scholar containing keywords cancer therapy resistance, phenotypic, metabolic and epigenetic factors, were vigorously searched, retrieved and analyzed. Results: Cancer cells have developed a range of cellular processes, including uncontrolled activation of Epithelial- Mesenchymal Transition (EMT), metabolic reprogramming and epigenetic alterations. These cellular processes play significant roles in the generation of therapy resistance. Furthermore, the microenvironment where cancer cells evolve effectively contributes to the process of chemoresistance. In tumour microenvironment immune cells, Mesenchymal Stem Cells (MSCs), endothelial cells and cancer-associated fibroblasts (CAFs) contribute to the maintenance of therapy-resistant phenotype via the secretion of factors that promote resistance to chemotherapy. Conclusion: To conclude, as these factors hinder successful cancer therapies, therapeutic resistance property of cancer cells is a subject of intense research, which in turn could open a new horizon to aim for developing efficient therapies.
Keywords: cancer heterogeneity